Spectroscopic Characterization of Mineralogy and Its Diversity Across Vesta - De Sanctis, M. C.; Ammannito, E.; Capria, M. T.; Tosi, F.; Capaccioni, F.; Zambon, F.; Carraro, F.; Fonte, S.; Frigeri, A.; Jaumann, R.; Magni, G.; Marchi, S.; et al. (Science, 2012)
A New Dawn Since 17 July 2011, NASA's spacecraft Dawn has been orbiting the asteroid Vesta—the second most massive and the third largest asteroid in the solar system (see the cover). Russell et al. (p. 684 ) use Dawn's observations to confirm that Vesta is a small differentiated planetary body with an inner core, and represents a surviving proto-planet from the earliest epoch of solar system formation; Vesta is also confirmed as the source of the howardite-eucrite-diogenite (HED) meteorites. Jaumann et al. (p. 687 ) report on the asteroid's overall geometry and topography, based on global surface mapping. Vesta's surface is dominated by numerous impact craters and large troughs around the equatorial region. Marchi et al. (p. 690 ) report on Vesta's complex cratering history and constrain the age of some of its major regions based on crater counts. Schenk et al. (p. 694 ) describe two giant impact basins located at the asteroid's south pole. Both basins are young and excavated enough amounts of material to form the Vestoids—a group of asteroids with a composition similar to that of Vesta—and HED meteorites. De Sanctis et al. (p. 697 ) present the mineralogical characterization of Vesta, based on data obtained by Dawn's visual and infrared spectrometer, revealing that this asteroid underwent a complex magmatic evolution that led to a differentiated crust and mantle. The global color variations detailed by Reddy et al. (p. 700 ) are unlike those of any other asteroid observed so far and are also indicative of a preserved, differentiated proto-planet.